Are sham‐operated mice a valid comparator in studies using a bladder outlet obstruction model? A pitfall reveals a meaningful insight. (12th December 2020) - Kitta, Takeya; Hattori, Tsuyoshi; Chiba, Hiroki; Higuchi, Madoka; Kanno‐Kakibuchi, Yukiko; Ouchi, Mifuka; Togo, Mio; Abe‐Takahashi, Yui; Michishita, Mai; Kitano, Tatsuya; Kusakabe, Naohisa; Shinohara, Nobuo
Abstract : Objective: To evaluate voiding behavior characteristics in intact and sham mice, and to examine whether intact mice show changes in "normal" micturition with aging. Methods: A total of 72 8‐week‐old mice were divided into two groups – intact and sham – and the latter group was subjected to a sham of partial bladder outlet obstruction surgery. Urination frequency was evaluated (through metabolic cages) at 1, 2, 3, 6 and 12 months after the surgery (or at the equivalent time points for the intact mice). To address possible mechanisms for aging and surgical effects on urinary behavior, quantitative real‐time polymerase chain reaction assays were carried out. Primary data were evaluated using scatter plots and descriptive statistics. Results: In sham mice, urination frequency showed strong variation at the earlier post‐surgical time points (especially at 1 month), with variation decreasing with time. Quantitative real‐time polymerase chain reaction showed that the serotonin 2C receptor‐encoding mRNA accumulated to >28‐fold higher levels at 24 months compared with 3 months in intact mice. A major limitation of the quantitative real‐time polymerase chain reaction experiments was that we did not separate whole bladder into muscle and mucosa. Conclusions: Although a sham operation is typically used in partial bladder outlet obstruction experiments to provide control animals, the sham group might itself show increased variation in micturition frequency at early times after surgery, compared with intact animals.